2005
DOI: 10.1107/s1600536805001686
|View full text |Cite
|
Sign up to set email alerts
|

1-(4-Chlorophenyl)-3-(4-hydroxyphenyl)prop-2-en-1-one

Abstract: In the title mol­ecule, C15H11ClO2, the ketone group is in the s‐cis conformation with respect to the olefinic double bond. The two aromatic rings form a dihedral angle of 26.07 (8)°. Screw‐related mol­ecules are linked via O—H⋯O hydrogen bonds, forming a chain along the c axis. Weak C—H⋯O and C—H⋯Cl interactions interconnect the chains into a three‐dimensional network.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
7
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 10 publications
6
7
0
Order By: Relevance
“…The bond lengths and angles are within normal ranges (Allen et al, 1987) and similar to those observed in other comparable structures (Jeyabharathi et al, 2002;Patil et al, 2006;Ravishankar et al, 2005;Sathiya Moorthi, Chinnakali, Nanjundan, Radhika et al, 2005;Sathiya Moorthi, Chinnakali, Nanjundan, Santhi et al, 2005;Sathiya Moorthi, Chinnakali, Nanjundan, Selvam et al, 2005;Sathiya Moorthi, Chinnakali, Nanjundan, Unnithan et al, 2005;Teh et al, 2006). The short H5Á Á ÁH8 (2.28 Å ) contact causes the bond angle C9-C10-C11 [123.08 (9) ] to deviate significantly from 120 .…”
Section: Commentsupporting
confidence: 82%
“…The bond lengths and angles are within normal ranges (Allen et al, 1987) and similar to those observed in other comparable structures (Jeyabharathi et al, 2002;Patil et al, 2006;Ravishankar et al, 2005;Sathiya Moorthi, Chinnakali, Nanjundan, Radhika et al, 2005;Sathiya Moorthi, Chinnakali, Nanjundan, Santhi et al, 2005;Sathiya Moorthi, Chinnakali, Nanjundan, Selvam et al, 2005;Sathiya Moorthi, Chinnakali, Nanjundan, Unnithan et al, 2005;Teh et al, 2006). The short H5Á Á ÁH8 (2.28 Å ) contact causes the bond angle C9-C10-C11 [123.08 (9) ] to deviate significantly from 120 .…”
Section: Commentsupporting
confidence: 82%
“…The bond lengths and angles for (I) are within normal ranges (Allen et al, 1987) and are comparable to those in related structures (Sathiya Moorthi, Chinnakali, Nanjundan, Radhika et al, 2005;Sathiya Moorthi, Chinnakali, Nanjundan, Santhi & Fun, 2005;Sathiya Moorthi, Chinnakali, Nanjundan, Selvam et al, 2005;Sathiya Moorthi, Chinnakali, Nanjundan, Unnithan et al, 2005;Ravishankar et al, 2005;Teh et al, 2006;Ng et al, 2006;Patil et al, 2006). The dihedral angle between the benzene rings is 18.34 (13) .…”
Section: Commentsupporting
confidence: 73%
“…Bond lengths and angles in (I) have normal values (Allen et al, 1987) and are comparable to those in related structures (Sathiya Moorthi, Chinnakali, Nanjundan, Santhi et al, 2005;Sathiya Moorthi, Chinnakali, Nanjundan, Unnithan et al, 2005;Sathiya Moorthi, Chinnakali, Nanjundan, Radhika et al, 2005;Ravishankar et al, 2005;Teh et al, 2006;Patil et al, 2006;Ng et al, 2006;Rosli et al, 2006). The least-squares plane through the enone group makes dihedral angles of 13.88 (24) and 9.78 (24) with the C1-C6 and C10-C15 benzene rings, respectively.…”
Section: Commentsupporting
confidence: 66%